Antibacterial Activity of Microalgae Dunaliella salina, Tetraselmis chuii and Isochrysis galbana Against Aquatic Pathogens - Ita Widowati; Muhammad Zainuri; Hermin Pancasakti Kusumaningrum; Yann Hardivillier (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
Recently, expanded consideration has been paid to the business and potentiality of microalgae. Some microalgae are at present being studied for their capacity to find important metabolites for the drug industry or aquacultural applications. Concerning these biotechnological challenges, there is a consistent exertion accommodated in both finding and taking advantage of new microalgal assets and fostering their putative business results or modern valorizations. The crude methanol extracts of three microalgae, Dunaliella salina, Tetraselmis chuii, and Isochrysis galbana, have been investigated for antibacterial activity using the disk diffusion method against aquatic pathogens of fish, shrimp, and shellfish e.g. Pseudomonas fluorescence and Vibrio harveyi. This research aimed to analyze the antibacterial activity of crude extract of these microalgae against aquatic pathogens. The disk diffusion method was used to investigate the antibacterial activity. The result showed that only T. chuii has the inhibition zone for both tested bacteria P. fluorescence and V. harveyi with the inhibition zone of 3.0 ± 0.6 mm on 100 µg. g–1 of extract concentration and 4.20 ± 1.1 mm against P. fluorescence on 10000 µg. g–1 of extract concentration. While D. salina and I. galbana have inhibition zone only for V. harveyi with the inhibition zone of 4.4 ± 0.6 mm and 3.2 ± 0.7 mm on 10000 µg. g–1 of extract concentration. These three microalgae may have potential use in aquatic pathogens as antimicrobial agents. It would be possible to develop biologically active compounds of microalgae as a functional feed for aquaculture.